PARTISIPASI MAHASISWA MEMBENAHI PASAR TRADISIONAL MAJAPAHIT YANG TERLANTAR AKIBAT PANDEMI COVID 19 - Nurokhman, Nurokhman; Widayanti, Lili; Kristiyanto, Hery (Gemi: Jurnal Penelitian dan Pengabdian, 2021)
The Majapahit Traditional Market is a market that was initiated by residents as a local populist economy urban in the Kaliurang tourist area of ​​Mount Merapi, Sleman, Yogyakarta. The concept of a market with tourist content packaged as a money transaction model is replaced by “dono” like ancient times to attract visitors. The area whose land belongs to the residents with local wooden and bamboo turban buildings is increasingly becoming a feature of the market appearance. As a result of the COVID-19 pandemic with the PPKM Government Regulation, the market which has only been running for 9 months since November 2019 has made the abandoned market abandoned by traders and managers. This condition has attracted the attention of Civil Engineering students, FT UCY, to contribute and first help to fix the market through the Thematic Community Service Program. The purpose of the activity is to fix market support facilities and increase the motivation of managers to maintain the market. The method used is a site survey, analyzing needs and carrying out physical activities at the market location. By knowing that some of the facilities were damaged and had not been equipped, then through coordination between students, field supervisors and market managers, activities in the form of repainting the kiosk, stage, sitting room, spot shelfi and gate. The addition of the required facilities in the form of a classic model of bamboo trash can, a classic model of hand washing, an information board. For joint maintenance, student work, field supervisors and traders are carried out. The need for facilities that still need to be continued as a service program for the provision of clean water pipelines, water towers and faucets.